Homo Sovieticus’s Post Humanism - a Picture of Dehumanization in Svietlana’s Alexievich’s Reportages: Chernobyl Prayer: A Chronicle of the Future and Secondhand Time: The Last of the Soviets. - Kózka, Michał (Sensus Historiae, 2020)
The aim of this paper is to present and interpret two Svietlana’s Alexievich’s reportages: Chernobyl Prayer: A Chronicle of the Future and Secondhand Time: The Last of the Soviets. Their author observes the post-soviet society from the closest perspective, meanwhile diagnoses its’ chances for revitalization. Based on articles and research of experts, as well as philosophical essays, from the 20th century, the paper presents analyses and interpretations of Belarusian writer’s artworks. They, hopefully, should contribute to expand the scientific fields in critique of post humanism.